Physiological adaptations to high-intensity interval and continuous training in kayak athletes - Papandreou, A.; Philippou, A.; Zacharogiannis, E.; Maridaki, M. (The Journal of Strength and Conditioning Research, 2020)
High-intensity interval training (HIIT) seems to be more effective than continuous training (CT) for the improvement of physical condition and sports performance. This study compared physiological adaptations with HIIT and CT in flat water kayak athletes. Twenty-four national-class kayakists were divided into 3 groups (n = 8 per group), 2 of which participated in an 8-week CT or HIIT program, whereas the third one served as control (C). An incremental maximum oxygen uptake (Vo2max), a maximal anaerobic Wingate-type, as well as 1,000-m (T1,000 m) and 200-m (T200 m) time test were performed before and after the training period on a kayak ergometer, to determine changes in Vo2max, peak blood lactate ([La+2]peak), paddling speed at Vo2max (PSVo2max), heart rate at Vo2max (HRpeak), paddling economy speed (PEs; speed at 75% of Vo2max), paddling speed at anaerobic ventilatory threshold (PSVT2), maximal paddling speed (PSpeak), and reduction of PSpeak (PSR). Vo2max, [La+2]peak, HRpeak, and PSR did not change after the 8-week training compared with baseline in either training group (p > 0.05). However, significant changes were found in PSVT2 and T200 m (HIIT), PSVo2max, PEs, PSpeak, and T1,000 m (CT and HIIT) (p < 0.05-0.0001) as compared to baseline. Moreover, percent changes were different between the training groups in PEs, and between control and training groups in PSpeak and PSVo2max (p < 0.05-0.01). Both training programs improved physiological and performance variables; however, HIIT resulted in significant changes of PSVT2 and T200 m and higher improvement of PEs with 15 times less training time compared with CT. Thus, HIIT seems more time-efficient than CT for improving paddling economy of kayaking performance.